Study of Serum C-reactive Protein as Prognostic Factor in Patients with Cerebrovascular Accidents - Nikhil Giri; Rakesh Patel; Karan Kapur (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Cerebrovascular accident may trigger the inflammatory response, increasing serum c-reactive protein (CRP) level. High CRP levels may be related to poor outcomes. We aimed to study the relationship between serum CRP levels in patients with cerebrovascular accidents and its outcome.Material and methods: A total of 154 subjects of CVA were screened for the diagnostic and prognostic significance of serum CRP using Barthel index scoring and the National Institute of Health Stroke Scale on admission and the seventh day of admission.Results: There was a significant rise in CRP levels in patients with stroke at the time of admission (p<0.001). More than 73% of total cases showed increased CRP levels at the time of admission. The National Institute of Health Stroke Scale (NIHSS) and Barthel index are good tools to assess the functional outcome of patients following a stroke with the rise in CRP levels.Conclusions: Our study showed the short-term prognostic value of Serum c-reactive protein. The study showed that CRP concentration is an independent predictor of severity after cerebrovascular accidents. Thus, developing new neuroprotective therapies, if targeted to modulate cytokine-induced inflammation, could be a promising way to prevent early deterioration in acute stroke.